MENTAL HEALTH AND ACADEMIC SUCCESS: A STUDY OF NURSING STUDENT-TEACHERS IN ISLAMABAD (The Research of Medical Science Review, 2024)
This study investigates the relationship between mental health and academic performance among nursing student-teachers in Islamabad. Recognizing that mental well-being significantly influences educational outcomes, the research examines how factors such as stress, anxiety, and depression affect students’ academic success. Through surveys and interviews, data was collected from nursing programs to assess mental health status and academic achievements. The findings reveal a notable correlation between poor mental health and declining academic performance, highlighting the challenges faced by these student-teachers. The study underscores the need for targeted mental health support and interventions within educational institutions to enhance both student well-being and academic success.